Encyclopedia of artificial intelligence - Rabunal, Juan Ramon 1973-; Dorado, Julian 1970-; Pazos Sierra, Alejandro (Gale virtual reference library, 2009)
Examines the most recent developments in the field covering theoretical developments, techniques, technologies, and applications of systems using intelligent characteristics for adaptability, automation learning, classification, prediction, and even artistic creation.